2020
DOI: 10.1371/journal.pone.0236488
|View full text |Cite|
|
Sign up to set email alerts
|

Caring for children with neurodevelopmental disability: Experiences from caretakers and health workers in rural eastern Uganda

Abstract: Background Long term outcomes of children with neurodevelopmental disability are influenced by the condition itself, available health services and caretakers' coping ability to nurture the children which may be related to their beliefs and experiences. Most children with neurodevelopmental disabilities live in resource constrained settings. To inform design of contextually appropriate interventions, this study explored health workers' and caretakers' experiences in caring for infants with neurodevelopmental di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The contrast is likely because in this study, phone-based CBT was led by peer mentors who were also caregivers of children with disabilities. Given that caregivers of children with disabilities face varied challenges, the peer mentors in this study were well-equipped to provide targeted psychosocial support, improving their mentees’ well-being [ 41 ]. It follows that group-based CBT may not have been sensitive to the vast challenges associated with caring for children with varied disabilities, as was the case for home caregivers in this study [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The contrast is likely because in this study, phone-based CBT was led by peer mentors who were also caregivers of children with disabilities. Given that caregivers of children with disabilities face varied challenges, the peer mentors in this study were well-equipped to provide targeted psychosocial support, improving their mentees’ well-being [ 41 ]. It follows that group-based CBT may not have been sensitive to the vast challenges associated with caring for children with varied disabilities, as was the case for home caregivers in this study [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study found that caretakers of CWDs who received informal social support had higher resilience than those who received formal social support [40]. Another quantitative study which used the same multidimensional scale to examine the association between social support and parental stress among caretakers of CWDs in Brazil, found no association between informal social support and perceived stress [41]. On the other hand, a qualitative study was conducted among caretakers of children with autism in Australia, and it found that caretakers increasingly relied on formal social over a period of nine years [42].…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, breast and cervical cancer screening in some LMICs has led to the discovery that detection of cancer —rather than producing a favorable response focused on treatment —can lead to social stigma ( Suwankhong and Liamputtong 2016 ; Nyblade et al, 2017 ). There is also evidence that in some LMIC contexts children diagnosed with a neurocognitive disability can face parental neglect and even sometimes abandonment ( Paget et al, 2016 ; Namazzi et al 2020 ). Guidance on returning IFs recognizes that “cultural norms surrounding certain diseases may be different in low-resource settings” ( Sullivan and Berkman 2018 ) and thus the plan for managing IFs needs to address social and cultural stigma that might emerge if abnormalities are detected and communicated.…”
Section: Core Elsi Issues In Designing and Conducting Field-based Mri Research In Remote And Resource-limited International Settingsmentioning
confidence: 99%